2015
DOI: 10.31436/iiumej.v16i2.604
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Battery Technology for Ev-Hev Panel: A Pioneering Study

Abstract: Global trends toward CO2 reduction and resource efficiency have significantly increased the importance of lightweight materials for automobile original equipment manufacturers (OEM). CO2 reduction is a fundamental driver for a more lightweight automobile. The introduction of Electrical Vehicles (EVs) is one initiative towards this end. However EVs are currently facing several weaknesses: limited driving range, battery pack heaviness, lack of safety and thermal control, high cost, and overall limited efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Moreover, it has several benefits, such as (1) being lightweight, (2) storing and supplying on-demand energy, and (3) providing external heat insulators for the vehicle body. Studies showed that by implementing this technology, the energy storage size can be reduced significantly [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has several benefits, such as (1) being lightweight, (2) storing and supplying on-demand energy, and (3) providing external heat insulators for the vehicle body. Studies showed that by implementing this technology, the energy storage size can be reduced significantly [10].…”
Section: Introductionmentioning
confidence: 99%
“…The rechargeable battery and supercapacitor i.e., ESD (Energy Storage Device) provides continuous electrical power in electric motors to operate an EV. The ESD such as supercapacitors or batteries are playing a vital part in the hybrid electric vehicle (HEV), plug-in HEV and EV to microgrid [2][3][4]. Becouse, some small urban city and rural area are started to produce electricity by utilizing the renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%